Innovations in Application of Professional Skills Development among Supply Chain Managers - Istomina, Anna; Vinogradova, Marina; Lukyanova, Anna; Bozhko, Lesya; Prodanova, Natalia (International Journal of Supply Chain Management, 2020)
Abstract— Professional competencies required in the field of logistics and supply chain management (SCM) are in the process of continuous development since the modern business environment creates a high demand for them. This study was aimed at assessing the state of training systems’ development and the capabilities for their future improvement in terms of creating conditions for effective SCM by skilled labor. In order to achieve the research objective, a comparative analysis of national higher training and logistics systems was performed on the example of Russia and Germany. During the investigation, statistical information, world ratings, and various publications in the public domain were used. These data allowed examining the relationship between the academic environment and SCM practice. Thus, a conclusion was made that a low level of interaction with industrial partners slows down innovation and creates obstacles for managers’ effective preparation. The gap between business and training is the main reason for insufficient qualification of SCM personnel and, as a result, poor logistic performance.